Website Wrapped By Gea Jual Beli Thrift Dan Preloved - Nur Hafizha; Dini Faisal (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of designing the Wrapped by Gea Website is to create a media that is more informative, effective in promotion and increases consumer trust and also to reach a wider market but also makes it easier for owners to convey information on marketed goods to prospective buyers and provide an attractive website page display. The Glass Box method is the method used in this study where this method always tries to determine the facts and the factual causes or reasons that underlie the design of the Wrapped By Gea website. In the process of data analysis in the design of the Wrapped By Gea website using 5W + 1H analysis which aims to determine and solve the problems encountered and find solutions to these problems. In the process of designing the user experience website, observations have been made on the habits and desires of the users, as well as the results of observations and studies are compiled and made with a simple layout that is easy to understand. The design that is made produces a main media for web design Wrapped by Gea. This web design is designed in a simple way with a simple, good, and easy to understand layout and flow, so that users do not find it difficult when running the website. In addition to the main media for the Wrapped by Gea web design, a supporting media was also created to support the main media, namely Promotional Videos, Social Media, Paper Bags, Stickers, X-Banners, Posters, and Lanyards.